Pool Boiling of Novec-649 on Inclined Microchannel - Robert Kaniowski (Energies, 2023)
Significant amounts of heat flow can be removed with small temperature differences by boiling. This process is used in a variety of industries, e.g., cooling electronics, digital circuits, power sources, etc. Heat dissipation from equipment that generates significant heat flows involves the movement of thermal energy through a wall into a cooling fluid. In the present study, this mechanism was analysed during the boiling of Novec-649 fluid at atmospheric pressure. The heat transfer surfaces were samples made of copper with milled, parallel grooves with a depth of 0.3 mm and a width ranging from 0.2 to 0.5 mm in 0.1 mm increments for straight channels and channels inclined with respect to the vertical by 30° and 60°, respectively. The study was carried out from the onset of nucleate boiling, approximately q = 7 kWm−2 with a heat flux increase until the critical heat flux was reached. The maximum heat flux was 262 kWm−2 and the heat transfer coefficient was 19.4 kWm−2K−1, achieved for surfaces with straight microchannels. A maximum heat flux increased by 80% and a heat transfer coefficient twice as high compared to a smooth surface was obtained. The performance of the experiment can be deemed adequate, considering that it compares well with the correlation results of different authors.